Design of an orthopaedic-specific discharge summary. Issue 1 (December 2016) - Soong, Christine; Kurabi, Bochra; Exconde, Kathleen; Tajammal, Faiqa; Bell, Chaim
Abstract Background Patients undergoing orthopaedic procedures experience major changes in function and daily routines upon their return home. Discharge summaries are an important communication tool that may play a role in optimizing a safe transition from hospital. Current care gaps and key elements of an ideal discharge summary specific for orthopaedic population are unknown. We sought to identify the challenges of current orthopaedic discharge summaries and to determine key elements of an ideal document. Methods Qualitative study survey using semi-structured interviews with a sample of 17 patients and clinicians representing diverse professions, backgrounds, and practice settings. We used the constant comparative method of qualitative analysis to define the experiences and perceptions of quality gaps and strategies to improve orthopaedic-specific discharge summaries. Results We identified 3 major themes describing factors perceived to be limiting the quality of current discharge summaries: 1) physician-centric documentation and the absence of a comprehensive, inter-professional perspective; 2) access to resources and health informatics; and 3) process variations in document creation and dissemination. Conclusions Clinicians and patients identified several factors limiting the quality of discharge summaries among orthopaedic inpatients. Incorporating these elements could improve hospital transitions.